Primary functioning hepatic paraganglioma mimicking hepatocellular carcinoma: A case report and literature review. Issue 17 (April 2018) - Liao, Wei; Ding, Ze-yang; Zhang, Binhao; Chen, Lin; Li, Gan-xun; Wu, Jing-jing; Zhang, Bixiang; Chen, Xiao-ping; Zhu, Peng
Abstract: Introduction: Hepatic paraganglioma (HPGL) originates from the sympathetic nervous tissue in the liver, and is an extremely rare type of the sympathetic paragangliomas. Till now, only 11 HPGL cases have been reported. Case presentation: A 49-year-old woman presented to our hospital with a lesion in the right lobe of the liver, which grew from 2 to 6 cm in 2 years. In addition, she had a 6-year history of diabetes. The patient was initially diagnosed as hepatocellular carcinoma and hepatectomy was performed. Surgical resection of the liver lesion was successful, but the blood pressure rose and fell sharply when the lesion was being removed. The pathological examination of the liver lesion showed that it was HPGL. After the operation, the patient recovered uneventfully. Follow-up examination showed the blood glucose level went back to the normal range in 20 days after the operation, and MRI and 131 I-MIBG scan showed that there was no evidence of recurrence and metastasis in >2 years. Conclusion: By means of reporting this case and reviewing 11 reported cases, we conclude that the incidence of HPGLs is extremely low and the clinical and radiological characteristics of HPGLs are nonspecific; thus, it is hard to diagnose HPGLs correctly. Surgical resection is curative therapy for HPGLs, whereas the removing of HPGLs may cause the releasing of catecholamine, and then lead to hypertension crisis and arrhythmia. Thus, antihypertensive therapy is necessary during the operation. Follow-ups after the operation are important for HPGL patients, for pathological examinations are not sufficient to differ malignant HPGLs from benign ones, and follow-ups are helpful for HPGL patients to find the recurrent foci or metastases timely.